Soursop (Annona muricata L.) and sugar apple (Annona squamosa L.): Antioxidant activity, fatty acids profile and determination of tocopherols - Luzia, Débora Maria Moreno [UNESP]; Jorge, Neuza [UNESP] (Emerald, 2012)
Purpose: This study aims to analyze the soursop and sugar apple seeds as to its composition, to evaluate the antioxidant potential of seeds extract and characterize the oil extracted from them, regarding the fatty acids profile and content of tocopherols. Design/methodology/approach: To obtain the extracts, dried and crushed seeds were extracted with ethanol for 30 minutes, at a ratio of 1:3 (m/m, seed: ethyl alcohol) under continuous stirring at room temperature. Then, the mixture was filtered and the supernatants subjected to rotoevaporator at 40°C aiming to determine, by direct weighing, the yields of dry extracts. Findings: According to the results, the soursop and sugar apple seeds constituted significant sources of lipids, proteins and carbohydrates and can therefore be used in food and feed, and offer relevant antioxidant activity of phenolic compounds. The oil seeds are a good source of unsaturated fatty acids, especially oleic and linoleic acids and they have significant amounts of total tocopherol. Research limitations/implications: Implications are the identification of bioactive compounds extracted from seeds of tropical and subtropical fruits, and to prevent certain types of diseases. Practical implications: The information presented might be directly used for developing of functional foods such as fruits. Originality/value: The article tries to identify new source of compounds extracted from fruits. © Emerald Group Publishing Limited.
Keywords: Antioxidants; Bioactive compounds; Fruits; Gas and liquid chromatography; Vegetables oils